First report of kleptoparasitism in Leptodeira rhombifera (Squamata, Dipsadidae) for a yellow toad Incilius luetkenii (Anura, Bufonidae) in Nicaragua - Milton Salazar-Saavedra; Rogemif D. Fuentes (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2025)
Kleptoparasitism is a widely observed feeding strategy across various animal taxa. In snakes it is well documented in captivity, but rarely reported in the wild. This observation is the first of its kind in Nicaragua. This behavior may be more common in wild snake populations than previously thought.